Improvement of Yarn Quality by Placing an Additional Compacting Device Between the Stretching Rollers in A Ring Spinning Machine - Alijon Yusupov; Husankhon Bobojanov; Sabirjon Yusupov; Muxriddin Yo‘ldoshev; Muslima Jurayeva (Genius Journals, 2022)
This article focuses on improving the physical and mechanical properties of yarns obtained on a ring spinning machine. The properties of the 27-tissue yarn obtained by placing a device that thickens the flow of fibres between the stretching pairs of the ring spinning machine and the quality indicators of the yarns produced at the enterprise were compared. Tables and graphs show the improvement of yarn quality parameters after installing the additional device on the ring-spinning machine. As a result of practical research, the coefficient of variation of the unevenness of spun yarns has improved by 1%, and thin areas of the yarn (Thin -30 % km) have improved by 5%, knots of the yarn (Neps, 200% /km) have improved by 4%
Keywords: yarn; hairiness; yarn unevenness; linear density